Pemodelan Tarikan Perjalanan Kawasan Perdagangan Jasa Skala Kecil di Jalan Sukun Raya Banyumanik - Yudi Basuki; Sri Rahayu; Novia Windri Rahmawati (Jurnal Pembangunan Wilayah dan Kota, 2020)
Banyumanik sub-district grows and develops caused by increases in population. Jalan Sukun Raya is a road commonly used by residents in Srondol Wetan Village to Jalan Setiabudi and vice versa. Sukun Raya Road Corridor is one of the local roads in Banyumanik Subdistrict.  The land use in this corridor is a commercial and service area, and settlement. Land use in the road corridor is a commercial and service area. Based on these problems, it is necessary to do trip attraction modeling. In this case, the trip attraction is needed in considering the impact of existing development, such as in the sub-center of the commercial and services area, housing, and offices. The aims of this article to develop the trip attraction model.Trip attraction modeling uses multiple linear regression analysis with the stepwise method on the commercial and service area and small scale on Jalan Sukun Raya, Banyumanik Subdistrict which is a sub-service area of the city of Semarang. Correlation and multiple linear regression analysis done based on data obtained from survey results. Data collection on Jalan Sukun Raya at peak times was carried out with field observations and interviews with established resource persons.The results showed that the sales income variable became the most influential variable on the trip attraction shown in the equation Y = 0.352 + 4.998E-7 X4. The resulting model is useful for estimating trip attraction in small-scale commercial and service areas.